Bi‐Functional Fe3O4/Au/CoFe‐LDH Sandwich‐Structured Electrocatalyst for Asymmetrical Electrolyzer with Low Operation Voltage. Issue 46 (15th October 2021) - Sun, Fengchao; Zhou, Yan; You, Zihan; Xia, Hanhan; Tuo, Yongxiao; Wang, Shutao; Jia, Cuiping; Zhang, Jun
Abstract: The reduction of the overall electrolysis potential to produce hydrogen is a critical target for fabricating applicable hydrogen evolution cells. Sandwich‐structured Fe3 O4 /Au/CoFe‐LDH is synthesized via a spontaneous galvanic displacement reaction. A series of structural characterizations indicate the successful synthesis of sandwich‐structured Fe3 O4 /Au/CoFe‐LDH electrocatalyst. The trace amount of Au laying between Fe3 O4 and CoFe‐LDH significantly improves the intrinsic conductivity and catalytic activity of the composite catalyst. In‐depth investigations indicate that Fe3 O4 and CoFe‐LDH are responsible for the electrocatalytic hydrogen evolution reaction (HER) whereas Au is responsible for the electrocatalytic glucose oxidation (GOR). The electrocatalytic tests indicate Fe3 O4 /Au/CoFe‐LDH offers excellent electrocatalytic activity and stability for both HER and GOR, even at high current density (i.e., 1000 mA cm −2 ). Further electrochemistry examinations in a two‐compartment cell with a two‐electrode configuration show that Fe3 O4 /Au/CoFe‐LDH can significantly reduce the overall potential for this asymmetrical cell, with only 0.48 and 0.89 V required to achieve 10 mA cm −2 current density with and without iR ‐compensation, which is the lowest overall potential requirement ever reported. The design and synthesis of Fe3 O4 /Au/CoFe‐LDH pave a new way to electrochemically produce hydrogen and gluconate under extremely low cell voltage, which can readily match with a variety of solar cells. Abstract : A bi‐functional Fe3 O4 /Au/CoFe‐LDH sandwich‐structured catalyst is used in an asymmetrical electrochemical cell for electrocatalytic hydrogen evolution reaction (HER) and glucose oxidation reaction (GOR) in alkali solution. 10 mA cm −2 current density is achieved by a cell voltage of 0.48 V. 89.7% selectivity of GOR is maintained even at 1000 mA cm −2 .